Defect-induced formation mechanism for boron nitride nanosheets-nanotubes hybrid structures. (October 2019) - Wang, Heng; Zhang, Shaowei; Li, Yawei; Wang, Weimin; Wang, Hao; Fu, Zhengyi
Abstract: Considering the defects effect and advanced hybrid nanostructures, this work proposes a novel mechanism to synthesize boron nitride (BN) nanosheets-nanotubes hybrid structures by catalytic chemical vapor deposition. Results show that the BN nanotubes with many lattice defects on the outer wall were initially formed by a vapor-liquid-solid mechanism. Subsequently, the BN nanosheets in-situ precipitated and grew along the BN nanotubes, bonding the nanotubes interfaces and forming the hybrid structures following a defect-induced mechanism. Overall, this mechanism is first proposed to form low-dimensional BN-based nanostructures, which serves as a promising basis for further research and development of BN nanosheets-nanotubes hybrid structures. Graphical abstract: Schematic illustration of the formation mechanism of boron nitride nanosheets-nanotubes hybrid structures.Unlabelled Image